Feasibility of using the position as feature for idea identification from text - Alksher, Mostafa Ahmed; Azman, Azreen; Yaakob, Razali; Abdul Kadir, Rabiah; Ali, Abdulmajid Hissen Mohamed; Alshari, Eissa Mohammed Mohsen (IEEE, 2018)
Abstracts of research papers are meant to provide a brief condensed overview of respective research topics. This includes a glimpse of the new idea that the paper proposes. The aim of the research presented here is to investigate the feasibility of the effect of text position in the idea identification. The abstracts are structured in the form of introduction, body, and conclusion. It is hypothesized that research ideas tend to be phrased in conclusion section of paper abstracts. 25 abstracts of the scientific papers were used to automatically identify the position of ideas within abstract sections. The results support the notion that the conclusion of the abstracts significantly represents the ideas.